2020
DOI: 10.1371/journal.pone.0228868
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, nature and predictors of omitted medication doses in mental health hospitals: A multi-centre study

Abstract: Objective Limited evidence concerning the burden and predictors of omitted medication doses within mental health hospitals could severely limit improvement efforts in this specialist setting. This study aimed to determine the prevalence, nature and predictors of omitted medication doses affecting hospital inpatients in two English National Health Service (NHS) mental health trusts. Methods Over 6 data collection days trained pharmacy teams screened inpatient prescription charts for scheduled and omitted medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Patient behaviors (e.g., aggression and consistent demanding) were recently identified by nursing professionals as one of the underlying causes of medication administration errors in this setting 32 . In another study, patients’ refusal to take medicines was found to be the most common reason for dose omissions in 2 English NHS mental health trusts 53 . Supporting measures should be put in place to help hospital staff and patients mitigate such challenging scenarios, which they may frequently experience in this setting 54,55 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Patient behaviors (e.g., aggression and consistent demanding) were recently identified by nursing professionals as one of the underlying causes of medication administration errors in this setting 32 . In another study, patients’ refusal to take medicines was found to be the most common reason for dose omissions in 2 English NHS mental health trusts 53 . Supporting measures should be put in place to help hospital staff and patients mitigate such challenging scenarios, which they may frequently experience in this setting 54,55 .…”
Section: Discussionmentioning
confidence: 96%
“…55 In another study, patients' refusal to take medicines was found to be the most common reason for dose omissions in two English NHS mental health trusts. 56 Supporting measures should be put in place to help hospital staff and patients mitigate such challenging scenarios which they may frequently experience in this setting. 57,58 Another important factor identified in this study was the lack of continuity of care when patients are transferred between different care settings or providers.…”
Section: Implications and Recommendations For Improvementmentioning
confidence: 99%
“…In recent years there has been increased attention in the published literature on medication safety for patients with mental illness in inpatient settings [15][16][17][18][19][20]. Unique risk factors associated with this patient group have been reported that can impact the safe use of medication including those related to patient-clinician relationships, patient behaviours, and impaired cognition [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Medication administration error is a high-risk situation during medicines management and with a median of 8.0% is the primary cause of medication harm. It is characterised by errors in the timing, omitted, and wrong doses of medication in various healthcare conditions and age groups 2,3 . A multicentre study in 38 hospitals in the UK on the prevalence, nature, and predictors of medication administration omissions using the MedsST tool indicated that medication administration omission was frequent and was influenced by the number of administered medications to patients 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by errors in the timing, omitted, and wrong doses of medication in various healthcare conditions and age groups. 2,3 A multicentre study in 38 hospitals in the UK on the prevalence, nature, and predictors of medication administration omissions using the MedsST tool indicated that medication administration omission was frequent and was influenced by the number of administered medications to patients. 4 Therefore, the safety of medication administration is one of the most important initiatives for the improvement of patient safety in the healthcare system.…”
Section: Introductionmentioning
confidence: 99%